Institutional Challenges in Tax Collection in Rural and Urban Land Sectors in Indonesia - Tambunan, Maria R.U.D. (Economics Department, Faculty of Economic and Islamic Business, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
This study captures the challenges faced by local governments in collecting tax on land and building (PBB-P2). This research focuses on institutional/governance aspects, human resource capabilities and tax administration system as the key aspect on a policy implementation. This research uses qualitative approach and qualitative research method. Data collection was performed by literature studies. This research shows that for institutional aspects, the preparation of devolution designed by the central government has not been enable the local government to be ready in performing its responsibility. For the institutional aspect, the local government need to enhace its institutional capacity. For human resource capability, the quality and quantity of human resources are still inadequate therefore the intensification of potential tax revenue has not optimal, worsen by the mutation of staff prior to the succession of leader. For administration aspect, local governments have used of technology as the backbone of administration, with several obstacles; the lack of coordination among responsible institution, the need to update the database and lack of socialization for the community. Therefore, to successfully implement a policy, these three aspects play a crucial role, especially on institution aspect.